2010
DOI: 10.1177/0363546510364052
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome After Arthroscopic Meniscal Repair Versus Arthroscopic Partial Meniscectomy for Traumatic Meniscal Tears

Abstract: Arthroscopic meniscal repair offers significantly improved results for isolated traumatic meniscal tears regarding the long-term follow-up in osteoarthritis prophylaxis and sports activity recovery compared with partial meniscectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
310
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(334 citation statements)
references
References 48 publications
(52 reference statements)
9
310
3
6
Order By: Relevance
“…40,44 Candidates are active patients who have tibiofemoral joint line pain and usually less than 50 years of age, or in their fifties and athletically active. 62 The patient must be willing to follow the rehabilitation program, including protected weight bearing for up to 6 weeks. Those in whom complex tears are repaired must agree to avoid strenuous activities and deep knee flexion for 4 to 6 months to prevent tearing and failure of the repair.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,44 Candidates are active patients who have tibiofemoral joint line pain and usually less than 50 years of age, or in their fifties and athletically active. 62 The patient must be willing to follow the rehabilitation program, including protected weight bearing for up to 6 weeks. Those in whom complex tears are repaired must agree to avoid strenuous activities and deep knee flexion for 4 to 6 months to prevent tearing and failure of the repair.…”
Section: Indicationsmentioning
confidence: 99%
“…In the 5 years since our last update on this topic in the JOSPT, 22 further longer-term data have been published supporting both meniscus repair 30,48,62 and meniscus transplantation. 63,69,73,76,77 The operative techniques and rehabilitation programs remain relatively similar, as do the indications and contraindications.…”
mentioning
confidence: 99%
“…Short-and long-term results are good when compared to a subtotal meniscectomy [1][2][3]. Therefore, meniscal repair has become the treatment of choice for traumatic meniscal lesions located in the vascularised area [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Stein et al 9 reported on a series of patients who underwent root repair and found favorable preservation of the articular surface at long-term follow-up. Kim et al 10 expanded on this study, demonstrating superior clinical and radiographic findings of posteromedial meniscus root repair when compared with medial meniscectomy.…”
Section: Discussionmentioning
confidence: 99%